NEW AND ADDITIONAL SUIDAE (MAMMALIA) FROM UPPER SIWALIK SUBGROUP (PLIO-PLEISTOCENE) OF NORTHWESTERN INDIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A new species of Sus, S. choprai sp. nov., and some rare and additional fossil suids, viz. Potamochoerus theobaldi and Sus falconeri are described from Pinjor Formation of Upper Siwaliks of northwestern India. Sus choprai sp. nov. was a large and one of the most advanced of the Siwalik suids, showing adaptations to an open country habitat.
Keywords: Suidae; Upper Siwalik Subgroup; Pinjor Formation; Upper Pliocene-Middle Pleistocene; Northwestern India.